Genomewide binding of transcription factor Snail1 in triple‐negative breast cancer cells. Issue 7 (21st May 2018) - Maturi, Varun; Morén, Anita; Enroth, Stefan; Heldin, Carl‐Henrik; Moustakas, Aristidis
Abstract : Transcriptional regulation mediated by the zinc finger protein Snail1 controls early embryogenesis. By binding to the epithelial tumor suppressor CDH1 gene, Snail1 initiates the epithelial–mesenchymal transition (EMT). The EMT generates stem‐like cells and promotes invasiveness during cancer progression. Accordingly, Snail1 mRNA and protein is abundantly expressed in triple‐negative breast cancers with enhanced metastatic potential and phenotypic signs of the EMT. Such high endogenous Snail1 protein levels permit quantitative chromatin immunoprecipitation‐sequencing (ChIP‐seq) analysis. Snail1 associated with 185 genes at cis regulatory regions in the Hs578T triple‐negative breast cancer cell model. These genes include morphogenetic regulators and signaling components that control polarized differentiation. Using the CRISPR/Cas9 system in Hs578T cells, a double deletion of 10 bp each was engineered into the first exon and into the second exon–intron junction of Snail1, suppressing Snail1 expression and causing misregulation of several hundred genes. Specific attention to regulators of chromatin organization provides a possible link to new phenotypes uncovered by the Snail1 loss‐of‐function mutation. On the other hand, genetic inactivation of Snail1 was not sufficient to establish a full epithelial transition to these tumor cells. Thus, Snail1 contributes to the malignant phenotype of breast cancer cells via diverse new mechanisms. Abstract : Snail1 binds to several novel regulatory sites in the genome of triple‐negative breast cancer cells. Snail1 can either induce or repress several genes, including PPFIA1, CRB1, CPED1, and BMP6 . Knockout of Snail1 could not lead to complete loss of the mesenchymal features. However, Snail1 knockout profoundly reduced proliferation in the same cells.